2017
DOI: 10.1021/acs.jnatprod.7b00295
|View full text |Cite|
|
Sign up to set email alerts
|

Constituents of Polygala flavescens ssp. flavescens and Their Activity as Inhibitors of Human Lactate Dehydrogenase

Abstract: Four new flavonol glycosides (1-4), two oligosaccharides (5, 6), one α-ionone (7), and three triterpenoid saponins (8-10), together with four known secondary metabolites (11-14), were isolated from the aerial parts of Polygala flavescens ssp. flavescens. All structures were elucidated on the basis of their spectroscopic and spectrometric data. The isolates were assayed for their inhibitory activity against isoform 5 of human lactate dehydrogenase, and compound 11 (3,6'-di-O-sinapoylsucrose) showed an IC value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The inhibitory activities of n -hexane and methanol extracts are reported as IC 50 values (Table 1). Differently from the n -hexane extracts that proved to be inactive on LDH5, some of the methanol extracts showed promising inhibition potencies on the enzyme as reported for other phenolic compounds 34 . Control aerial part extracts displayed an IC 50 value of 2.1 mg/ml and it was less potent that the inoculated counterpart, that reached the best IC 50 value (0.9 mg/ml) among all the tested extracts, thus being even more potent that the corresponding inoculated root extract (IC 50 = 1.9 mg/ml).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The inhibitory activities of n -hexane and methanol extracts are reported as IC 50 values (Table 1). Differently from the n -hexane extracts that proved to be inactive on LDH5, some of the methanol extracts showed promising inhibition potencies on the enzyme as reported for other phenolic compounds 34 . Control aerial part extracts displayed an IC 50 value of 2.1 mg/ml and it was less potent that the inoculated counterpart, that reached the best IC 50 value (0.9 mg/ml) among all the tested extracts, thus being even more potent that the corresponding inoculated root extract (IC 50 = 1.9 mg/ml).…”
Section: Resultsmentioning
confidence: 75%
“…This study was carried out by using the molecular mechanics and Poisson–Boltzmann surface area (MM-PBSA) method 38 , which has been shown to accurately estimate the ligand-receptor energy interaction 39 . In this case the MM-PBSA calculations were used for discriminating among different poses suggested by a docking calculation 34,40 . This method averages the contributions of gas phase energies, solvation free energies, and solute entropies calculated for snapshots of the complex molecule as well as the unbound components, extracted from MD trajectories, according to the procedure fully described in the Experimental Section.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibitory activities of the newly synthesized sugar conjugates were measured as IC 50 values on purified human enzyme isoform h LDH5 (Table 2). Galloflavin was used as reference compound, because it is a well-known phenolic LDH inhibitor which is often used in enzymatic LDH assays [27,28], since it is easily synthesizable and it is also commercially available. Among the newly synthesized sugar conjugates, compounds 7α , 7β , and 10β , which are the glyco-conjugates bearing the N -hydroxyindole moiety at the anomeric position, showed a moderate inhibition potency towards h LDH5, with IC 50 values ranging from 229 to 246 μM, compared to the IC 50 values of the parent gluco-conjugate 2 (IC 50 = 112.8 ± 5.6 µM) and of its aglycone moiety 1 (IC 50 = 10.8 ± 3.5 µM) Conversely, compounds 13 , 18 , 19 , and 23 , in which the N -hydroxyindole portion is linked to the C(6) position of mono- or disaccharide units, were inactive at the maximum tested concentration of 500 μM.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the novel in silico approaches, the search for the most suitable anti-cancer agents starts from the structural configuration of the targeted molecule (transporter/enzyme) and uses bioinformatical tools such as molecular docking studies, drug-likeness property experiments, pharmacophore modeling, or molecular dynamics simulation studies in order to predict, as accurate as possible, new potential agents. As an example, for LDH, molecular docking studies have suggested gossypol, quercetin, luteolin, and ursolic acid [ 109 ] luteolin 7-O-β-d-glucoside [ 110 ], 3,6′-di-O-sinapoylsucrose, reiniose F [ 112 ], cannabichromene and Δ9-tetrahydrocannabinolic acid [ 25 ] just to mention a few natural potent ligands. However, the potential candidates obtained from in silico screenings must be confirmed in further in vitro/in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…The same strategy was implemented in the study of Polygala flavescens , where 3,6′-di-O-sinapoylsucrose and reiniose F were identified as potent LDH-5 inhibitors, with reported IC 50 values of 90.4 μM and 190.7 μM, respectively [ 112 ]. Wang et al [ 113 ] validated epigallocatechin’s effects on LDH-A activity and expression by in vitro enzymatic activity assay and western blotting.…”
Section: Natural Regulators Of Aerobic Glycolysismentioning
confidence: 99%